Fear of heights: an immersive VR approach with biosignals monitoring - Neves, Martim Daniel Ferreira (2023)
The human being is affected by several disorders, one of the most prevalent being anxiety disorders. One example of these disorders is a specific phobia, which is an overwhelming, yet irrational, fear of an object, place or situation. This condition can be an impairment in the lives of the phobic individuals because they go out of their way to avoid what causes the fear, which in turn will only aggravate the matter. Being an active field of study, exposure therapy is the quintessential treatment option for specific phobias, as proven by a plethora of studies. There are several types of exposure therapy and in vivo exposure is regarded as the most effective one. However, despite all its advantages, in vivo exposure also has drawbacks, like cost and excessive levels of stress during exposure. The recent introduction of Virtual Reality (VR) to the mainstream allowed it to be explored for new purposes, other than entertainment. As such, a new type of exposure therapy (Virtual Reality Exposure Therapy) saw an increase in usage and several studies about its effectiveness were conducted. It has been proven that Virtual Reality Exposure Therapy can be as effective as in vivo exposure, while at the same time being cheaper, safer and easier to present the desired stimulus. In this dissertation, we propose Up(Date) Your Fear, an affordable and portable system that can be used as an alternative/complement to the traditional in vivo therapy. The system uses VR to present height related stimuli to phobic individuals and monitors their physiological response using an external device (electrocardiogram - ECG and Respiration). The stimuli are presented under the form of an open-world game, allowing the individuals to explore the world and stimuli at their own pace. The system also supports data storage, processing and visualization. By performing two user studies it was possible to verify the system’s usability and stimuli’s efficacy in the generation of a cardiovascular response by the user. This response was verified in every participant, even the ones who previously didn’t report fear of heights, and that states the efficacy of the stimuli and the validity of the system.